Pendidikan Karakter Anak Pada Keluarga Bercerai - Moh. Toriqul Chaer; Azam Syukur Rahmatullah; Sukatin (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2022)
Abstract: Every parent wants their child to be a person with a good personality, a healthy mental attitude, and a commendable character. As the first personal shaper in a child's life, parents must be an example for their children. The object of this research is three divorced families in Ploso, Kendal, Ngawi, East Java. The method used is qualitative. The procedure for collecting data uses the following techniques: interviews, observation, and documentation. Based on the results of the study, it can be concluded that: 1) There are two parenting styles of divorced parents in educating their children, namely: a) democratic parenting with attitudes: mutual respect and respect, always discussing children's problems, providing opportunities for children to be independent, close relationships, b) Permissive Parenting with attitudes: parental attention is lacking for children, children are allowed to develop without parental guidance, children's interests are not prioritized, children are allowed to act and do as they please, children always get whatever they want. 2) The characteristics of children from divorced parents include: a) children become awkward in facing the realities of life, b) children sometimes dream of becoming famous, c) children prefer to fantasize about their lives, d) children have less imagination when they are playing, and e) the child experiences disturbances in social, cognitive and personality development. Abstrak: Setiap orang tua pasti menginginkan anaknya menjadi orang yang berkepribadian baik, sikap mental yang sehat serta berakhlak yang terpuji. Orang tua sebagai pembentuk pribadi yang pertama dalam kehidupan anak, harus menjadi teladan bagi anak-anaknya. Objek penelitian adalah 3 keluarga yang bercerai di Desa Ploso Kendal, Ngawi, Jawa Timur. Metode yang digunakan metode kualitatif. Prosedur pengumpulan data dengan teknik: wawancara, observasi dan dokumentasi. Berdasarkan hasil kajian dapat disimpulkan bahwa: 1) Pola asuh orang tua yang bercerai dalam mendidik anaknya ada dua yaitu: a) pola asuh demokratis dengan sikap: saling menghargai dan menghormati, selalu mendiskusikan masalah anak, pemberian kesempatan anak agar mandiri, hubungan yang akrab, b) Pola Asuh Permisif dengan sikap: perhatian orang tua yang kurang terhadap anak, anak dibiarkan berkembang tanpa bimbingan orang tua, prioritas kepentingan anak tidak diutamakan, Anak dibiarkan bertindak dan sesuka hatinya, anak selalu memperoleh apapun yang dia inginkan. 2) Karakter anak dari orang tua yang bercerai antara lain: a) anak berubah menjadi canggung menghadapi kenyataan hidup, b) anak kadang-kadang bermimpi menjadi orang yang tenar, c) anak lebih suka berkhayal tentang hidupnya, d) anak imajinasinya berkurang saat mereka bermain, dan e) anak mengalami gangguan dalam perkembangan sosial, kognitif dan kepribadiannya.